Synthesis, characterisation and hirshfeld surface analysis of phosphanecopper(I) acylthiourea complexes / Mohamad Zarif Mohd Zubir - Mohamad Zarif, Mohd Zubir (2019)
A series of phosphanecopper(I) complexes of acylthiourea derivatives have been synthesised and characterised by a combination of FTIR spectroscopic studies, NMR spectroscopic studies, X-ray crystallography and Hirshfeld surface analysis. One series of thirteen acylthiourea ligands of the type N-benzoyl-N’-(R-substituted phenyl)thiourea, where R is H, 3-Me, 3-OMe, 3-OH, 3-Cl, 2-Me, 2-OMe, 2-OH, 2-Cl, 4-Me, 4-OMe, 4-OH, 4-Cl denoted by T1-T13 respectively, have been synthesised and verified spectroscopically. These series of ligand (T1-T13) was then followed by a complexation step with a copper(I) salt and triphenylphosphine to form the phosphanecopper(I) complexes of N-benzoyl-N’-(R-substituted phenyl)thiourea, given the complexes formula of, [Cu(T)(I)(PPh3)] designated by CT1-CT13 respectively. All the complexes were characterised spectroscopically, and some were with X-ray crystallography. Results from spectroscopic data and some with crystal structure analysis show that in all complexes the acylthiourea ligands coordinated as monodentate S-donor mode. The crystallisation of complexes from acetonitrile yielded good prismatic, yellow single crystals suitable for X-ray crystallography. The complexes CT1-CT7 showed a distorted tetrahedral with a single acylthiourea ligand, two triphenylphosphine act as a co-ligand and one iodide anion. The acylthiourea ligands behaved as a hypodentate S-donor ligand instead of its common O, S-bidentate nature due to the tetrahedrally favoured geometry of the copper(I) centre and the presence of two bulky group of triphenylphosphine ligand as the co-ligand. It was obtained that CT1-CT4 and CT7 crystals crystallised in the monoclinic P21/c crystal system whereas CT5 and CT6 crystallised in triclinic P1̅crystal system. The isostructural structures of these two crystal systems illustrated almost similar crystal packing but with significantly different interactions as determined by Hirshfeld surface analysis.